Pengaruh Kepemimpinan, Motivasi, dan Disiplin Kerja Terhadap Kinerja Karyawan pada Rumah Sakit Tlogorejo Semarang - Dida Pramudya Darmansa; Askar Yunianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Performance is the most important human resource for any organization. Human resources are a key element in the development process of an organization and in achieving its goals. The main aim of the research is to find out how leadership, motivation and work discipline of Torogorejo Hospital Semarang staff influence their performance. The primary data provided was obtained from a questionnaire. The subjects of this research were employees of RS Tologorejo Semarang. The research used random sampling techniques and obtained results from 100 employees. The tests used in this research are factor analysis for validity testing, Cronbach alpha measurement for reliability testing, and multiple regression equations for hypothesis testing. The research results show that leadership, motivation and work discipline have a positive effect on performance.